Physicochemical and Organoleptic Characteristics of Snack Bars (Study: Proportion of Flaxseed Flour : Red Rice Flour and Addition of Honey - Rifky Andri Pratama; Sarofa, Ulya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Snack bars are practical rod-shaped food products generally made from a mixture of nutritious ingredients and consumed as a source of energy and nutrients. The purpose of this study was to determine the optimal treatment combination of flaxseed flour and brown rice flour, supplemented with honey, to produce snack bars with the most beneficial nutritional properties. This study employed a Completely Randomised Design (CRD) with a factorial pattern, involving two factors and three replications. Factor I: flaxseed flour: brown rice flour (20%: 80%; 25%: 35%; 30%: 70%) and factor II: the addition of honey (40%; 45%; 50%). The Data were analysed using ANOVA and Duncan’s Multiple Range Test (DMRT) to determine if there were significant differences at a 5% level, while the organoleptic data were analysed using the Friedman Test at a 5% level. Treatment of flaxseed flour proportions : brown rice flour (30%; 70%) and the addition of honey (40%) is the best treatment that produces a snack bar with the characteristics of water content 12.38%, ash content 2.35%, protein content 11.78%, fat content 8.78%, crude fiber content 5.95%, carbohydrate content 64.57%, total calories 386 (kcal/100 grams), hardness texture 6.388 (N), chewiness texture 189.891, and taste organoleptic test 4.80 (neutral), color 5.00 (like), aroma 4.90 (neutral), texture 4.73 (neutral). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-Being